2014
DOI: 10.1002/atr.1261
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of demand‐adapted railway timetables

Abstract: Railway scheduling and timetabling are common stages in the classical hierarchical railway planning process and they perhaps represent the step with major influence on user's perception about quality of service. This aspect, in conjunction with their contribution to service profitability, makes them a widely studied topic in the literature, where nowadays many efforts are focused on improving the solving methods of the corresponding optimization problems. However, literature about models considering detailed d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(45 citation statements)
references
References 25 publications
0
45
0
Order By: Relevance
“…Even though the relative weights of these three antecedents of intention are expected to vary with the kind of behavior being predicted and with the conditions under which the behavior is to be taken. A lot of literature have confirmed that attitude, subjective norms and perceived behavior control have strong, direct, and positive effect on intentions [10]. Hypothesis 1.…”
Section: The Theory Of Planned Behaviormentioning
confidence: 86%
See 1 more Smart Citation
“…Even though the relative weights of these three antecedents of intention are expected to vary with the kind of behavior being predicted and with the conditions under which the behavior is to be taken. A lot of literature have confirmed that attitude, subjective norms and perceived behavior control have strong, direct, and positive effect on intentions [10]. Hypothesis 1.…”
Section: The Theory Of Planned Behaviormentioning
confidence: 86%
“…The theory of planned behavior (TPB) is a well-researched model which is widely used in explaining and in predicting human behavior across a variety of disciplines [10], such as marketing consumer behavior [13], leisure behavior [17], and disease prevention [24]. Thus, TPB proposes that three key constructs will drive behavior: attitude, subjective norms and perceived behavior control.…”
Section: The Theory Of Planned Behaviormentioning
confidence: 99%
“…These are based on the design of saturated schedules and use mathematical programming models that achieve a high degree of saturation and simultaneously ensure certain level of quality of service (Canca et al, 2014a). Different techniques have been used for this purpose: branch-and-bound (Szpigel, 1972;Jovanovic and Harker, 1991), heuristic algorithms (Cai and Goh, 1994;Carey and Lockwood, 1995), tabu search (Higgins et al, 1996), Lagrangian relaxation (Caprara et al, 2000), and linear programming (Mussone and Wolfter Calvo, 2013).…”
Section: Optimization Methodsmentioning
confidence: 99%
“…The vertical load factor VLF is 100%, corresponding to the section of higher occupancy (ratio 290/290). The load factor LF is HLF Á VLF ¼ 0:7331 (Canca et al, 2014a). Finally, the percentage of users who do not require transfers is 100%.…”
Section: Problem Description and Illustrationmentioning
confidence: 99%
“…On the other hand, it is also easy to transform periodic to non-periodic timetables using the unfolding technique, where the dependency between events in different periods is still reserved (Goverde, 2007;van der Meer, 2008). Additionally, partially periodic and non-periodic train services are also being adopted in practical train operations in Europe and China to cope with the non-uniformly distributed demand and exceptional situations, where the non-periodic expression would be applicable (Caimi et al, 2011;Forsgren et al, 2011;Wong et al, 2008;Canca et al, 2014;Cacchiani et al, 2014).…”
Section: Max-plus System For a Railway Networkmentioning
confidence: 98%